Analisis Pengaruh Parameter Infill Pattern dan Nozzle Temperature terhadap tensile strength Filamen PLA PRO - Zaldy S. Suzen; Riskullah Dirga Trisaplin; Hasdiansah Hasdiansah (Manutech : Jurnal Teknologi Manufaktur, 2022)
3D Printing is part of Rapid Prototyping technology, where the printing process converts a 3D design into a solid object, can be held and has volume, the formation is done by placing the filament layer by layer. The purpose of this study was to determine the effect of the process parameters used, to determine the highest and lowest tensile strength values ??and to determine the eligible parameters for car dashboard production. The method in this study using the factorial method multiplied by 15 types of infill and 3 temperature levels so as to create a total of 45 specimens, then replicated 3 times to make 135 samples of specimens, the process parameters used were 15 types of infill and 3 levels of nozzle temperature that were printed in a vertical orientation. The highest tensile strength value is 43.9 MPa with the parameter (infill pattern) 3D honeycomb, nozzle temperature 210?C, and the lowest tensile strength value is 14.7 MPa with the parameter (infill pattern) archimedean chord, nozzle temperature 220?C. The final result of the research shows that there is an influence between parameters on the value of tensile strength and recommends several parameters that can be used to produce car dashboards.